Is CRT pro-arrhythmic? A comparative analysis of the occurrence of ventricular arrhythmias between patients implanted with CRTs and ICDs - Gopalamurugan, A. B.; Ganesha Babu, G.; Rogers, Dominic P.; Simpson, Adam L.; Ahsan, Syed Y.; Lambiase, Pier D.; Chow, Anthony W.; Lowe, Martin D.; Rowland, Edward; Segal, Oliver R. (Frontiers in Physiology, 2014)
Aim and Hypothesis: Despite the proven symptomatic and mortality benefit of cardiac resynchronisation therapy (CRT), there is anecdotal evidence it may be pro-arrhythmic in some patients. We aimed to identify if there were significant differences in the incidence of ventricular arrhythmias in patients undergoing CRT-D and ICD implantation for primary prevention indication. We hypothesised that CRT is unlikely to be pro-arrhythmic based on the positive mortality and morbidity data from large randomized trials. Methods and Results: A retrospective analysis of device therapies for ventricular arrhythmia (VA) in a primary prevention device cohort was performed. Patients with ischemic (IHD) and non-ischemic (DCM) cardiomyopathy and implantable cardioverter-defibrillators (ICD) or CRT+ICD devices (CRT-D) implanted between 2005 and 2007 without prior history of sustained ventricular arrhythmia were included for analysis. VA episodes were identified from stored electrograms and defined as sustained (VT/VF) if therapy (anti-tachycardia pacing (ATP) or shocks) was delivered or non-sustained (NSVT) if not. Of a total of 180 patients, 117 (68% male) were in the CRT-D group, 42% IHD, ejection fraction (EF) 24.5±8.2% and mean follow-up 23.9± 9.8 months. 63 patients (84% male) were in the ICD group, 60% IHD, EF 27.7±7.2% and mean follow-up 24.6±10.8 months. Overall, there was no significant difference in the incidence of ventricular arrhythmia (35.0% vs. 38.1%, p = 0.74), sustained VT (21.3% vs. 28.5%, p=0.36) or NSVT (12.8% vs. 9.5%, p=0.63) and no significant difference in type of therapy received for VT/VF: ATP (68% vs. 66.6%, p=0.73) and shocks (32% vs. 33.3%, p=0.71) between the CRT-D and ICD groups, respectively. Conclusion: In patients with cardiomyopathy receiving CRT-D and ICDs for primary prophylaxis, there was no significant difference in the incidence of ventricular arrhythmia. From this single centre retrospective analysis, there is no evidence